Preparation method of high-stability MOFs (Metal-Organic Frameworks) with thermodynamic metastable-state ordered defect
Through the method of high equivalent metal salts and modulators, the ordered defective MOFs in thermodynamic metastable state are synthesized, which solves the problem of random defect distribution in the prior art, and achieves high stability and excellent catalytic and adsorption properties.
Patent Information
- Application Number
- CN202411832996.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The prior art is difficult to achieve orderly defect synthesis of high-stability MOFs, resulting in random defect distribution, destroying the order of MOFs, and hindering the research on the structure-performance relationship.
Thermodynamic metastable ordered defective MOFs are synthesized by the method of high-equivalent metal salt and high-equivalent modulator, and the steps of ultrasonic treatment, hydrothermal reaction, solvent exchange and vacuum activation treatment.
The synthesis of new structures of orderly defects has been achieved, with a larger specific surface area and pore size, and more open metal sites, which significantly improves the catalytic and adsorption properties.
Smart Images

Figure CN119431820A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of defect or metastable MOFs synthesis, and relates to a method for preparing highly stable MOFs thermodynamically metastable ordered defects, and specifically to obtaining ordered defect MOFs by using a high equivalent metal salt and a high equivalent modulator. Background Art
[0002] Metal-organic frameworks (MOFs) are an attractive research field with important applications in gas storage, sensing, catalysis and other fields. Defects are inherent properties of solid crystalline materials and play a key role in determining and influencing material properties. As a crystalline porous material, MOFs are no exception and are affected by defects. Defect engineering has become a powerful tool for adjusting and optimizing the performance of MOFs (see Daliran, S., et al. Defect-enabling zirconium-based metal–organic frameworks for energy and environmental remediation applications. Chem. Soc. Rev. 53, 6244-6294 (2024)). Although there are many studies on controlling the number and type of defects, achieving precise control of defect distribution remains a major challenge (see Han, Y., et al. Tracebenzene capture by decoration of structural defects in metal–organic framework materials. Nat. Mater. 23, 1531-1538 (2024)). At present, the distribution of defects is random, which destroys the order of MOFs and hinders the study of structure-performance relationships. Current synthesis methods, especially de novo synthesis, make it difficult to achieve a controllable distribution of defects. It is still a major challenge to achieve ordered defects that conform to the thermodynamic metastable phase, especially highly stable MOFs.
[0003] The present invention proposes a method for preparing highly stable ordered defect MOFs, and obtains a new structure with ordered defects. This method can be extended to a variety of metals and ligands. Ordered defect MOFs have better application performance than defect-free and disordered defect MOFs, such as in catalysis, adsorption, etc. Summary of the invention
[0004] The purpose of the present invention is to address the shortcomings and deficiencies in current synthesis technology and propose a method for preparing highly stable ordered defect MOFs.
[0005] The technical solution of the present invention:
[0006] A method for preparing thermodynamically metastable ordered defects of highly stable MOFs, comprising the following steps:
[0007] (1) preparing a high equivalent metal salt solution I, adding the high equivalent metal salt solution I to a high equivalent monocarboxylic acid which is kept stirred, and then performing ultrasonic treatment;
[0008] (2) preparing ligand solution II, adding ligand solution II to a mixed solution of a high equivalent monocarboxylic acid and a metal salt, stirring and sealing, and performing a hydrothermal reaction; cooling naturally to room temperature after the hydrothermal reaction, filtering the obtained solid, and washing with a solvent;
[0009] (3) performing solvent exchange on the solid obtained in step (2), and then performing activation treatment on the solid after solvent exchange under vacuum to obtain a solid having a structural composition of M x O y L z MOFs structure, where M = alkaline earth metal, third group metal, transition metal such as Zr, Hf, Y, Eu, etc.; L = polycarboxylic acids of different lengths such as fumaric acid, terephthalic acid, biphenyl dicarboxylic acid, and polycarboxylic acids modified with different types and numbers of functional groups; M x O y L z The MOFs structure is a ligand:cluster material ratio of L:M x =z:1 (z=1-8), each cluster has an ordered defect structure with multiple open metal sites.
[0010] The molar ratio of the metal salt, the monocarboxylic acid and the ligand is (5-30):(125-500):1.
[0011] The metal salt is an alkaline earth metal salt, a third group metal salt, or a transition metal salt such as Zr, Hf, Y, or Eu.
[0012] The ligands are polycarboxylic acids of different lengths such as fumaric acid, terephthalic acid, biphenyl dicarboxylic acid, and polycarboxylic acids modified with different types and numbers of functional groups.
[0013] The monocarboxylic acid is formic acid or acetic acid.
[0014] The solvents used to prepare the metal salt solution I and the ligand solution II are both N,N-dimethylformamide or N,N-dimethylacetamide.
[0015] The temperature of ultrasonic treatment is 20°C-50°C, and the time is 20-50 minutes.
[0016] The temperature of the hydrothermal reaction is 100°C-150°C, and the time is 36-72h.
[0017] The solvent exchange is to use a solvent and methanol to exchange the solid in sequence, the solvent is the same solvent used in step (1) and step (2), and the stirring time is 12-24 hours.
[0018] The temperature of the activation treatment under vacuum is 90-150°C and the time is 10-24h.
[0019] Beneficial effects of the present invention:
[0020] 1. The present invention realizes the synthesis of a new structure with ordered defects by assembling thermodynamically metastable ordered defect MOFs under the conditions of high concentrations of monocarboxylic acid and metal salts through self-template induced nucleation and lattice matching growth mechanism. Compared with the defect structure, the structure has ordered defects, larger specific surface area, pore size and open metal sites.
[0021] 2. By replacing different proportions of metal salts and ligands, MOFs with ordered defects can be obtained.
[0022] 3. The new structure with ordered defects synthesized in the present invention has more open sites and larger pores than the disordered defect structure, and significantly improves the performance in catalysis, adsorption, etc., such as Lewis acid catalysis reactions such as hydrolysis of nerve agent simulants, ring opening of styrene oxide, and carbon dioxide cycloaddition. Since more open sites and larger pores caused by ordered defects are more conducive to substrate diffusion, the catalysis of the reaction is promoted. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the XRD image of the ordered defective MOFs synthesized in Example 1.
[0024] Figure 2 This is the XRD image of the ordered defective MOFs synthesized in Example 2.
[0025] Figure 3 This is the thermogravimetric curve of the ordered defective MOFs synthesized in Example 1.
[0026] Figure 4 This is the nitrogen adsorption isotherm image of the ordered defect MOFs synthesized in Example 1.
[0027] Figure 5 This is a scanning electron microscope image of the ordered defective MOFs synthesized in Example 1.
[0028] Figure 6 This is the XRD image of the disordered defect MOFs synthesized in Comparative Example 1.
[0029] Figure 7 This is the XRD image of the disordered defect MOFs synthesized in Comparative Example 2.
[0030] Figure 8 This is the XRD image of the disordered defect MOFs synthesized in Comparative Example 3. DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.
[0032] Example 1
[0033] The preparation method of highly stable ordered defect MOFs comprises the following steps:
[0034] (1) Add 60 mL of N,N-dimethylformamide and 9.6 mmol of zirconium chloride into a beaker and stir ultrasonically to accelerate dissolution to obtain solution I;
[0035] (2) Add 3 mL of formic acid to a 30 mL glass bottle, transfer Solution I to the 30 mL glass bottle while stirring, and after sufficient stirring, transfer the 30 mL glass bottle to an ultrasonic oscillator for ultrasonic treatment;
[0036] (3) Add 16 mL of N,N-dimethylformamide and 1.28 mmol of terephthalic acid into a beaker and stir to dissolve to obtain solution II;
[0037] (4) Take out the 30 mL glass bottle after ultrasonic treatment, add solution II into the glass bottle while stirring, seal it and put it into an oven for hydrothermal reaction at 120°C for 72 hours;
[0038] (5) taking out the glass bottle after the reaction in step (4) and cooling it naturally to room temperature, filtering out the obtained solid and washing it with N,N-dimethylformamide several times;
[0039] (6) The solid obtained in step (5) was filtered out and solvent exchanged with N,N-dimethylformamide and methanol, and the sample after solvent exchange was activated under vacuum at an activation temperature of 90° C. for 20 h.
[0040] Example 2
[0041] The preparation method of highly stable ordered defect MOFs comprises the following steps:
[0042] (1) Add 60 mL of N,N-dimethylformamide and 19.2 mmol of zirconium chloride into a beaker and stir ultrasonically to accelerate dissolution to obtain solution I;
[0043] (2) Add 6 mL of formic acid to a 30 mL glass bottle, transfer Solution I to the 30 mL glass bottle while stirring, and after sufficient stirring, transfer the 30 mL glass bottle to an ultrasonic oscillator for ultrasonic treatment;
[0044] (3) Add 16 mL of N,N-dimethylformamide and 1.28 mmol of terephthalic acid into a beaker and stir to dissolve to obtain solution II;
[0045] (4) Take out the 30 mL glass bottle after ultrasonic treatment, add solution II into the glass bottle while stirring, seal it and put it into an oven for hydrothermal reaction at 150°C for 24 h;
[0046] (5) taking out the glass bottle after the reaction in step (4) and cooling it naturally to room temperature, filtering out the obtained solid and washing it with N,N-dimethylformamide several times;
[0047] (6) The solid obtained in step (5) was filtered out and solvent exchanged with N,N-dimethylformamide and methanol, and the sample after solvent exchange was activated under vacuum at an activation temperature of 150° C. for 10 h.
[0048] Example 3: The zirconium chloride in step (1) of Example 1 is replaced by hafnium chloride, and the other conditions are the same as those of Example 1.
[0049] Example 4 The zirconium chloride in step (1) of Example 1 is replaced by europium nitrate, and the other conditions are the same as those of Example 1.
[0050] Example 5: The terephthalic acid in step (3) of Example 1 is replaced by methyl terephthalic acid, and the other conditions are the same as those of Example 1.
[0051] In Example 6, the terephthalic acid in step (3) of Example 1 is replaced by hydroxyterephthalic acid, and the other conditions are the same as those of Example 1.
[0052] Example 7: The terephthalic acid in step (3) of Example 1 is replaced by aminoterephthalic acid, and the other conditions are the same as those of Example 1.
[0053] In Example 8, the terephthalic acid in step (3) of Example 1 is replaced by methoxyterephthalic acid, and the other conditions are the same as those of Example 1.
[0054] Comparative Example 1
[0055] The preparation method of disordered defect MOFs comprises the following steps:
[0056] (1) Add 60 mL of N,N-dimethylformamide and 9.6 mmol of zirconium chloride into a beaker and stir ultrasonically to accelerate dissolution to obtain solution I;
[0057] (2) Add 1 mL of formic acid to a 30 mL glass bottle, transfer Solution I to the 30 mL glass bottle while stirring, and after sufficient stirring, transfer the 30 mL glass bottle to an ultrasonic oscillator for ultrasonic treatment;
[0058] (3) Add 16 mL of N,N-dimethylformamide and 1.28 mmol of terephthalic acid into a beaker and stir to dissolve to obtain solution II;
[0059] (4) Take out the 30 mL glass bottle after ultrasonic treatment, add solution II into the glass bottle while stirring, seal it and put it into an oven for hydrothermal reaction at 150°C for 24 h;
[0060] (5) taking out the glass bottle after the reaction in step (4) and cooling it naturally to room temperature, filtering out the obtained solid and washing it with N,N-dimethylformamide several times;
[0061] (6) The solid obtained in step (5) was filtered out and solvent exchanged with N,N-dimethylformamide and methanol, and the sample after solvent exchange was activated under vacuum at an activation temperature of 150° C. for 10 h.
[0062] Comparative Example 2
[0063] The preparation method of disordered defect MOFs comprises the following steps:
[0064] (1) Add 60 mL of N,N-dimethylformamide and 2.4 mmol of zirconium chloride into a beaker and stir ultrasonically to accelerate dissolution to obtain solution I;
[0065] (2) Add 3 mL of formic acid to a 30 mL glass bottle, transfer Solution I to the 30 mL glass bottle while stirring, and after sufficient stirring, transfer the 30 mL glass bottle to an ultrasonic oscillator for ultrasonic treatment;
[0066] (3) Add 16 mL of N,N-dimethylformamide and 1.28 mmol of terephthalic acid into a beaker and stir to dissolve to obtain solution II;
[0067] (4) Take out the 30 mL glass bottle after ultrasonic treatment, add solution II into the glass bottle while stirring, seal it and put it into an oven for hydrothermal reaction at 150°C for 24 h;
[0068] (5) taking out the glass bottle after the reaction in step (4) and cooling it naturally to room temperature, filtering out the obtained solid and washing it with N,N-dimethylformamide several times;
[0069] (6) The solid obtained in step (5) was filtered out and solvent exchanged with N,N-dimethylformamide and methanol, and the sample after solvent exchange was activated under vacuum at an activation temperature of 150° C. for 10 h.
[0070] Comparative Example 3
[0071] The preparation method of disordered defect MOFs comprises the following steps:
[0072] (1) Add 60 mL of N,N-dimethylformamide and 2.4 mmol of zirconium chloride into a beaker and stir ultrasonically to accelerate dissolution to obtain solution I;
[0073] (2) Add 1 mL of formic acid to a 30 mL glass bottle, transfer Solution I to the 30 mL glass bottle while stirring, and after sufficient stirring, transfer the 30 mL glass bottle to an ultrasonic oscillator for ultrasonic treatment;
[0074] (3) Add 16 mL of N,N-dimethylformamide and 1.28 mmol of terephthalic acid into a beaker and stir to dissolve to obtain solution II;
[0075] (4) Take out the 30 mL glass bottle after ultrasonic treatment, add solution II into the glass bottle while stirring, seal it and put it into an oven for hydrothermal reaction at 150°C for 24 h;
[0076] (5) taking out the glass bottle after the reaction in step (4) and cooling it naturally to room temperature, filtering out the obtained solid and washing it with N,N-dimethylformamide several times;
[0077] (6) The solid obtained in step (5) was filtered out and solvent exchanged with N,N-dimethylformamide and methanol, and the sample after solvent exchange was activated under vacuum at an activation temperature of 150° C. for 10 h.
[0078] Application Examples
[0079] The performance of highly stable ordered defect MOFs is significantly improved in applications such as catalysis and adsorption. Here, the Lewis acid-catalyzed reaction of the hydrolysis of a nerve agent simulant (DMNP) is taken as an example.
[0080] The steps are as follows: add a 10% D2O / H2O buffer solution of N-ethylmorpholine and Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 as catalysts in a reactor, wherein the catalyst ratio is 3 mol% of DMNP, and stir at room temperature until the dispersion is complete. Add DMNP to start the reaction, and take samples at 5, 10, 15, 20, and 30 minutes after the start of the reaction, and characterize them using nuclear magnetic resonance spectroscopy.
[0081] The results are as follows: Example 1 can convert 50% within 5 minutes, Comparative Example 1 can convert 22.5% under the same conditions, Comparative Example 2 can convert 23.9% under the same conditions, and Comparative Example 3 can convert 15.7% under the same conditions.
[0082] The results show that due to the existence of ordered defects, Example 1 produces more metal open sites and larger pore sizes, which are beneficial to the diffusion and hydrolysis of the substrate DMNP, so the conversion rate is higher in the same time.
Claims
1. A method for preparing highly stable MOFs thermodynamically metastable ordered defects, characterized in that: Here are the steps: (1) preparing a metal salt solution I, adding the metal salt solution I to a monocarboxylic acid which is kept stirred, and then performing an ultrasonic treatment; (2) preparing ligand solution II, adding ligand solution II to a mixed solution of monocarboxylic acid and metal salt, stirring and sealing, and performing a hydrothermal reaction; cooling naturally to room temperature after the hydrothermal reaction, filtering the obtained solid, and washing with a solvent; (3) performing solvent exchange on the solid obtained in step (2), and then performing activation treatment on the solid after solvent exchange under vacuum to obtain a solid having a structural composition of M x O y L z MOF structure, wherein M = alkaline earth metal, third main group metal, transition metal; L = polycarboxylic acid modified with functional groups of different lengths, types and numbers; M x O y L z The MOF structure is a ligand: cluster material ratio of L:M x =z:1, z=1-8, each cluster has an ordered defect structure with multiple open metal sites.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the metal salt, the monocarboxylic acid and the ligand is (5-30):(125-500):
1.
3. The preparation method according to claim 1, characterized in that: The metal salt is one of an alkaline earth metal salt, a third main group metal salt and a transition metal salt.
4. The preparation method according to claim 1, characterized in that: The ligand is one of polycarboxylic acids such as fumaric acid, terephthalic acid, and biphenyl dicarboxylic acid.
5. The preparation method according to claim 1, characterized in that: The monocarboxylic acid is formic acid or acetic acid.
6. The preparation method according to claim 1, characterized in that: The solvents used to prepare the metal salt solution I and the ligand solution II are both N,N-dimethylformamide or N,N-dimethylacetamide.
7. The preparation method according to claim 1, characterized in that: The temperature of the ultrasonic treatment is 20°C-50°C, and the time is 20-50 minutes.
8. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100°C-150°C, and the time is 36-72h.
9. The preparation method according to claim 1, characterized in that: The solvent exchange is to use a solvent and methanol to exchange the solid in sequence, the solvent is the same as the solvent used in step (1) and step (2), and the stirring time is 12-24 hours.
10. The preparation method according to claim 1, characterized in that: The temperature of the activation treatment under vacuum is 90-150° C. and the time is 10-24 hours.
Citation Information
Patent Citations
Free radical controllable-release defect coordination metal-organic framework, and preparation method and application thereof
CN110964207A
Defect type UiO-66 photocatalytic material, and preparation method and application thereof
CN113559936A
A defective metal-organic framework material, its preparation method and application
CN114931978A
Method for preparing high-defect titanium-based bimetal organic framework desulfurization catalyst from plasma and application of high-defect titanium-based bimetal organic framework desulfurization catalyst
CN118045634A
Imperfect mofs (IMOFS) material, preparation and use in catalysis, sorption and separation
WO2017210874A1